Building log book toolkit : a guide and templates for preparing building log books - Jones, Phil, 1954- (CIBSE, 2006)
The CIBSE Building log book tool kit templates offer a standard format for the summary. This covers how a building is intended to work and how it is meant to be maintained and serviced. They also provide a means to record the energy use and maintenance of the services within the building. -- Provided by publisher.
Keywords: Building management -- Handbooks, manuals, etc.; Facility management -- Handbooks, manuals, etc.; Buildings -- Energy consumption.; Buildings -- Environmental aspects.; elektronické knihy; electronic books